Prolonged Cardiopulmonary Bypass Time-Induced Endothelial Dysfunction via Glypican-1 Shedding, Inflammation, and Matrix Metalloproteinase 9 in Patients Undergoing Cardiac Surgery - Shiyi Li; Katherine V. Nordick; Iván Murrieta-Álvarez; Randall P. Kirby; Rishav Bhattacharya; Ismael Garcia; Camila Hochman-Mendez; Todd K. Rosengart; Kenneth K. Liao; Nandan K. Mondal (Biomedicines)
Objectives: A prolonged cardiopulmonary bypass (CPB) time of over 180 min is linked to poorer outcomes and higher mortality in cardiac surgery. This study examines how glypican-1 shedding, matrix metallopeptidase 9 (MMP9), and the pro-inflammatory cytokine IL-1β may contribute to endothelial dysfunction in patients undergoing on-pump surgery with an extended CPB. Methods: Fifty-one patients undergoing cardiac surgical procedures were divided into two groups based on the intraoperative CPB duration: (i) normal CPB (<180 min, n = 23) and (ii) prolonged CPB (>180 min, n = 28). The preoperative, intraoperative, and postoperative plasma levels of glypican-1, MMP9, and IL-1β were measured. Results: Before surgery, the plasma levels of glypican-1, MMP9, and IL-1β were comparable between the normal CPB and the prolonged CPB groups. However, after the end of the CPB, all three markers showed significant elevation in the prolonged CPB group compared to the normal CPB group. Significant correlations were observed between the intraoperative and postoperative levels of MMP9, IL-1β, and glypican-1. A strong positive correlation was also observed between the intraoperative and postoperative levels of glypican-1 and the duration of the CPB. Conclusions: A prolonged CPB triggers a systemic inflammatory response and activates MMP9, leading to glypican-1 shedding and endothelial dysfunction.